2016
DOI: 10.1039/c6ra24569b
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible titanate nanotubes with high loading capacity of genistein: cytotoxicity study and anti-migratory effect on U87-MG cancer cell lines

Abstract: International audienceTitanate nanotubes (Ti-Nts) have proved to be a potential candidate for drug delivery due to their large surface change and higher cellular uptake as a direct consequence of their tubular shape. Ti-Nts were assessed for their safety, their kinetics of cellular uptake on U87-MG cell line and for genistein loading efficiency. No cytotoxic effect was observed under higher empty Ti-Nts concentrations up to 100 mu g mL(-1). The multiwalled tubular morphology was found to be an important parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(55 citation statements)
references
References 41 publications
5
45
0
Order By: Relevance
“…Similarly, TiONts are widely studied [29][30][31] in a broad range of applications since their discovery in the late 1990s [32]. Recently, TiONt applications have been developed in several fields of biomedicine [29,33], such as orthopedics and dental implants [34], dopamine detection [35], DNA transfection [36] and adsorption [37], bioimaging [38,39], safe nanocarrier [36,40,41], drug delivery (genistein and docetaxel) [42][43][44], and cancer cell radiosensitization [44,45]. These TiONt applications are possible due to the atypical morphology shared with CNTs and HNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, TiONts are widely studied [29][30][31] in a broad range of applications since their discovery in the late 1990s [32]. Recently, TiONt applications have been developed in several fields of biomedicine [29,33], such as orthopedics and dental implants [34], dopamine detection [35], DNA transfection [36] and adsorption [37], bioimaging [38,39], safe nanocarrier [36,40,41], drug delivery (genistein and docetaxel) [42][43][44], and cancer cell radiosensitization [44,45]. These TiONt applications are possible due to the atypical morphology shared with CNTs and HNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Tubular nanoparticles are more readily internalized than their spherical counterparts of a similar volume. [18b,20] This is why our group, and some others, are developing TiONts for a variety of biomedical applications, such as dopamine detection, transfection,[20a] imaging, when conjugated with superparamagnetic iron oxide nanoparticles, drug delivery, and cancer cell radiosensitization . Our group has previously studied the internalization of TiONts in various cell lines (cardiomyocytes,[20a] CHO, SNB19 and U87MG), in which TiONts did not induce cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[21c,27,29] These modifications can also allow new functionalities to be added. [28b,30] To date, very few studies have investigated the functionalization of TiONts for biomedical applications: polyethylene glycol (PEG), polyethylene imine polymers or genistein have been grafted onto the surface of TiONts . Herein, TiONts were engineered as a theranostic nanoplatform since several molecules were grafted onto their surface for various purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, T. Baati et al have shown the effectiveness of a TiONt-based nanocarrier against glioblastoma multiform with a controlled administration of genistein (biologically active flavonoid) in glioblastoma cells (Baati et al 2016). This study showed that these TiONts have a drug loading efficiency of 51.2 wt% and allows a controlled release of the therapeutic agent.…”
Section: Tionts As New Nanocarriersmentioning
confidence: 92%